IDIOM DALAM BAHASA INGGRIS DAN BAHASA TONDANO: SUATU ANALISIS KONTRASTIF - Deeng, Astried Filistea Agustina; Pakasi, Jenny H.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ This study is entitled â€œIdioms in English and Tondanese: A Contrastive Analysisâ€. Idiom is a special feature that the meaning of idiom is very different from the literal meaning. This research is tu fulfill the requirement of accomplishing bachelorâ€™s degree in English Department Faculty of Humanities, Sam Ratulangi University. The aim of this research is to identify, analyze, and describe the types of the forms andÂ meaning of idioms in English and Tondanese, and investigate the similarities and differences of both languages. The writer used theory of Boatner and Gates (1975) and were contrasted to find the differences using Brown (1980: 149-150). The results of this study shows that there are 5 types of idiom in Tondanese, they are: lexemic idioms, phraseological idioms, proverbs, compound idiom and reduplication. It also shows that both languages have differences and similarities. Â Â Â Â Â Â Keyword: Idiom, English and Tondanese, Contrastive Analysis, form and meaning